Stress corrosion cracking of a circulation water heater tubesheet. (August 2017) - Khalifeh, A.R.; Dehghan Banaraki, A.; Daneshmanesh, H.; Paydar, M.H.
Abstract: After only three years' service of a circulation water heater, tubesheet showed sever leakage and led the plant to emergency shutdown. On-site investigation revealed extensive cracking initiated at weld area and through the tubesheet holes. Samples from failed area were removed and investigated. The chemical and micro structural properties were analyzed by optical and scanning electron microscopy. Micro structural observations have shown intergranular and transgranular crack growth. Sulfur was detected in corrosion products by EDS examinations. Sulfur compounds and chromium carbides also were detected by XRD analyses. Wet carbonaceous deposits were found on surfaces of the tube sheet. Analysis on the deposits depicted presence of caustic and chlorides. Considering all aspects of failures led to this conclusion that the material was in sensitized condition possibly due to overheating at the deposit sites. The sensitized material failed due to the acronym SCC induced by polythionic acid. Presence of chlorides and caustic aid the failures. Highlights: We evaluate root cause failure of an austenitic stainless steel heat exchanger. The heat exchanger failed due to SCC induced by polythionic acid. Residual stress produced by machining and welding aside operational thermal stress aid the failure.